Perception of Nurses toward Mental Health in Tadjuddin Chalid Hospital - Widiyawati, Wiwik; Yusuf, Ah; Ibnu, Indra Fajar (International Journal of Psychosocial Rehabilitation, 2020)
Bad assumption toward patients of mental health disorder is not only emerged from general population, but also arises in special populations such as health care providers, such as nurses. It needs measurement to nurses toward mental health disorder . this study has a purpose to observe the perception of nurses toward mental health problem. This study uses qualitative using descriptive approach. The sample of this study are 86 nurses of Dr Tadjuddin Chalid Hospital in Makassar, Indonesia. The reliability test results of the questionnaire using Cronbach Alpha. The result shows that most of the respondents have agreed opinions (57%) that mentally disorder people can do things appropriately. Most of the respondents have agreed opinions (77.9%) related to statements helping people solve their problems. Most of the respondents have agree opinions (74.4%) that respondents feel relieved when they able to complete the task on time. From the result, it can be concluded that all aspects of perception tend to be positive, only in the aspect of affection in the statement about pesimism, most of the participants are negative